2007
DOI: 10.1246/cl.2007.490
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropically Phase-segregated Co9S8/PdSx Nanoacorns: Stability Improvement and New Heterostructures

Abstract: Stability of anisotropically phase-segregated Co9S8/PdSx nanoacorns, which we recently prepared, was improved by the addition of oleic acid or oleylamine as a stabilizer. Further investigations on the experimental conditions implied the formation of more complex PdSx/Co9S8/PdSx and Co9S8/PdSx/Co9S8 heterostructured nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Also, a nanoforest of peptide nanotubes is known. [192] Al last, the following nanoforms could be artificially attributed (although their shape is not frequently similar to the shapes above) to a tree/forest/nature theme: nanoacorns { (Figure 32), CoPd sulfide (Figure 33), [193,194] }, nanolarvas (Figure 34), nanoflowers (Figure 35), examined in detail in a recent review, [195] and their nanobouquets, for example those of In 2 O [196] 3 or L-cysteinePb. [197] "Nanoanimal" structures, nanourchins, (Figure 36) which could be also considered as nanoflowers, are known mainly for vanadium oxides (VO x ), [198−200] as well as Zndoped SnO 2 (these nanourchins are assembled by the nanocones and have high photocatalytic activity efficiency; the solvotermal reaction mechanism for Zn-doped SnO 2 hierarchical architectures assembled by nanocones is proposed [201] ), CdTe, [202] and carbon, [203] and are reviewed, among other nanostructures, in.…”
Section: Gallery Of Relatively Rare Nanoformsmentioning
confidence: 99%
“…Also, a nanoforest of peptide nanotubes is known. [192] Al last, the following nanoforms could be artificially attributed (although their shape is not frequently similar to the shapes above) to a tree/forest/nature theme: nanoacorns { (Figure 32), CoPd sulfide (Figure 33), [193,194] }, nanolarvas (Figure 34), nanoflowers (Figure 35), examined in detail in a recent review, [195] and their nanobouquets, for example those of In 2 O [196] 3 or L-cysteinePb. [197] "Nanoanimal" structures, nanourchins, (Figure 36) which could be also considered as nanoflowers, are known mainly for vanadium oxides (VO x ), [198−200] as well as Zndoped SnO 2 (these nanourchins are assembled by the nanocones and have high photocatalytic activity efficiency; the solvotermal reaction mechanism for Zn-doped SnO 2 hierarchical architectures assembled by nanocones is proposed [201] ), CdTe, [202] and carbon, [203] and are reviewed, among other nanostructures, in.…”
Section: Gallery Of Relatively Rare Nanoformsmentioning
confidence: 99%
“…By varying the reaction temperature and time, it was possible to synthesize Cu−In sulfide nanocrystals with acorn, bottle, and larva shapes. The anisotropically phase-segregated CoPd sulfide nanoparticles, named by the authors as “CoPd nanoacorns” and consisting of crystalline Co 9 S 8 and amorphous PdS x phases with the Co 9 S 8 (001) plane at their interface, were spontaneously generated by reducing the corresponding metal precursors with 1,2-hexadecanediol in the presence of various alkanethiols. Their formation mechanism is presented in Figure . They were found to spontaneously form through the anisotropic growth of the Co 9 S 8 phase after the generation of PdS x nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Schematic illustration of the speculated formation mechanism of the CoPd nanoacorns. Reproduced with permission from ref . Copyright 2007 American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the Co 9 S 8 phases of the Co-Pd sulfide nanoparticles were unstable in solution as a result of the comparatively lower passivation by thiols, leading to the precipitation of the Co 9 S 8 phases and/or the partial coalescence of two Co 9 S 8 phases. [23] We consider that the key factor that determines whether the fusion of two Co 9 S 8 phases proceeds or not is the amount of the passivating agent, C 18 SH, present when growing the Co 9 S 8 phases. Figure 3 shows the TEM images of the resulting nanostructured materials obtained at C 18 SH/[Co(acac) 2 ] molar ratios of 2, 3, 5, and 10 (the amount of [Co(acac) 2 ] was fixed at 0.25 mmol).…”
mentioning
confidence: 99%